The Effect of Nonwoven Microfiber Substrate Polypropylene Thickness to Air Filtration Performance of Polyacrilonitrille Nanofiber - Rajak, Abdul; Syahputra, Tri Siswandi; Munir, Muhammad Miftahul; Khairurrijal, K. (Jurnal ILMU DASAR, 2019)
Since a nanofiber medium on itself is soft and fragile and cannot be used alone as air filters. Coating nanofiber on a rigid substrate to form a composite that can be handled readily is necessary. Beside can improve the filtration efficiency, adding the substrate will also save the use of nanofibers mat itself. The aim of this study is to evaluate the effect of substrate thickness on the performance of nanofibers mat in aerosol filtration in order to find the optimum thickness of substrate that can increase the quality of nanofiber filter. The substrate used was a low cost microfiber non-woven fabric made from polypropylene (PP). The nanofibers mat was composed of electrospun polyacrylonitrile (PAN) with concentration of 9 wt.% which dissolved at N,N dimethylformamide (DMF). Five variations of PP different in thickness was used as substrate. From the SEM image, it was found that there is increasing fiber diameter of PAN after electrospun into PP substrate. From the porosity estimation of each nanofiber, it was found that the porosity decreased with increasing the substrate thickness. For test the performance of nanofiber filter, the particles of polystyrene latex (PSL) which generated by atomizer was used as the aerosol particle. In addition, to evaluate the performance filter in PM2.5 filtration, the experiment was carried out with generate the smoke from burning incense. Air filtration performance of all variations is obtained by comparison the results of measurement including: pressure drop, efficiency and quality factor. From the results, there is limitation on the substrates thickness based on the value of the quality factor obtained. Overall, PP nonwoven as the substrates gives the great contribution on the efficiency of PAN nanofiber. Keywords: substrate, polypropylene, thickness, nanofiber, air filtration.